Memory for Hand-Use Depends on Consistency of Handedness - Edlin, James M.; Carris, Emily K.; Lyle, Keith B. (Frontiers in Human Neuroscience, 2013)
Individuals who do not consistently use the same hand to perform unimanual tasks (inconsistent-handed) outperform consistent right- and left-handed individuals on tests of episodic memory. We explored whether the inconsistent-hander memory advantage extends to memory for unimanual hand use itself. Are inconsistent-handers better able to remember which hand they used to perform actions? Opposing predictions are possible, stemming from the finding that some regions of the corpus callosum are larger in inconsistent-handers, especially those that connect motor areas. One hypothesis is that greater callosally-mediated interhemispheric interaction produces inconsistent-handers’ superior retrieval of episodic memories, and this may extend to episodic memories for hand use. Alternatively, we also hypothesized that greater interhemispheric interaction could produce more bilateral activation in motor areas during the performance and retrieval of unimanual actions. This could interfere with inconsistent-handers’ ability to remember which hand they used. To test these competing predictions in the current study, consistent- and inconsistent-handers performed unimanual actions, half of which required manipulating objects and half of which did not. Each action was performed 4 times in one of 5 conditions that differed in the ratio of left to right hand use: always left (4:0), usually left (3:1), equal (2:2), usually right (1:3), or always right (0:4). We compared consistent- and inconsistent-handers on recall of the left:right ratio for each action. Inconsistent-handers remembered how they performed actions better than consistent-handers, regardless of ratio. These findings provide another example of superior episodic retrieval in inconsistent-handers. We discuss how greater interaction might benefit memory for hand use.